E0183 Livin protects against cardiomyocyte apoptosis in anoxia/reoxygenation injury via p38-mediated signal pathway. (17th November 2010) - Ling, Chen; Kui, Hong; Jianxin, Hu; Xihu, Yin; Yun, Luo
Abstract : Introduction: Although anoxic preconditioning (APC) in the myocardium has been investigated for many years, its physiological mechanism is still not completely understood. Increasing evidence indicates that transiently increased resistance to ischaemic damage following APC is dependent on de novo protein synthesis. However, the key effector pathway(s) associated with APC still remains unclear. Livin, a member of the inhibitor of apoptosis protein (IAP) family, since IAP-mediated activation of JNK1, as well as protection against TNF-β and ICE-induced apoptosis. The detailed mechanism underlying its antiapoptotic function in cardiomyocytes has not yet been fully characterised. Objective: To investigate whether Linvin expression might be aberrantly induced in cardiomyocytes that were subjected to anoxia/reoxygenation (A/R) injury and to investigate whether Linvin might also contribute to cardio-protection after APC. Methods: We cloned a Linvin expression vector, transfected it into rat cardiomyocytes, and examined Linvin expression in rat cardiomyocytes that were subjected to A/R injury. Moreover, we studied the role of three major MAPK pathways, for example, p38 MAPK, JNK, and ERK1/2, in order to evaluate the molecular mechanism underlying Linvin up-regulation and A/R induced cardiomyocyte injury. Results: APC induced an up-regulation of Linvin and the transfection of Linvin gene into the cardiomyocytes attenuated A/R injury. The inhibition of p38 MAPK by SB203580 abolished both the Linvin up-regulation and the cardio-protection provided by APC. Conclusion: APC could act to protect the heart from A/R injury with cooperation from the Linvin in addition, it up-regulates Linvin expression through a p38 MAPK signalling pathway.